A low-corrosion-effect flame brazing auxiliary aluminum flux

CN122913728APending Publication Date: 2026-10-16SUZHOU BIANGU WELDING MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510408107.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0002]传统的氯化物型铝钎剂,如常见的LiCl-KCl-ZnCl2体系,虽具备较高的活性,能在一定程度上满足焊接过程中去除氧化膜的需求,但存在严重缺陷,其焊后残渣中含有的Cl⁻离子,会引发强烈的电化学腐蚀,对焊接后的铝及铝合金部件造成损害,影响其使用寿命和性能稳定性,并且,部分氯化物型钎剂配方中还含有PbCl2、CdCl2等重金属成分,不仅对操作人员健康构成威胁,还在废弃物处理环节带来极大的环保压力,难以符合当下日益严格的环保法规要求;

Benefits of technology

本发明通过特定比例的氟铝酸钾与氟铝酸铯形成490-520℃共晶基质,结合氟化锂与氟化锌构成的双活性增强体系,能够高效溶解氧化铝及氧化镁复合氧化膜,对含镁量高达1.8%的铝合金进行火焰钎焊时,焊缝抗拉强度达196-200MPa,气密性低至7×10-10-8×10-10Pa・m³/s,远超传统钎剂对含镁量的限制以及焊接质量标准,极大拓展了铝合金焊接的材料范围,满足了如航空航天、汽车制造等对焊接质量要求严苛的行业需求;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913728A_ABST
    Figure CN122913728A_ABST
Patent Text Reader

Abstract

The application discloses a low-corrosion-effect flame brazing auxiliary aluminum flux, and particularly relates to the technical field of aluminum and aluminum alloy flame brazing, and comprises the following components in percentage by mass: potassium fluoroaluminate 35-45% and cesium fluoroaluminate 10-15% form a eutectic matrix with a temperature of 490-520 DEG C, lithium fluoride 5-8% and zinc fluoride 3-6% constitute a double-active enhancement system, potassium chloride 20-25% is used as an interface regulator, hydroxypropyl methyl cellulose 0.5-1.5% and propylene glycol-polyethylene glycol 15-20% form an intelligent thixotropic carrier. The flame brazing auxiliary aluminum flux can realize efficient brazing of aluminum alloy containing 2.0% of magnesium, the tensile strength of the weld is greater than or equal to 195 MPa, the air tightness is good, the welding quality is good, the corrosion of the residue after welding is extremely low, the green process is used in preparation, and the fluorine recovery rate is greater than or equal to 98%. Due to the innovative preparation process, the welding time is shortened by more than 30%, the production efficiency is greatly improved, and the application potential is great in the fields of aerospace and automobile manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of flame brazing technology for aluminum and aluminum alloys, and more specifically, to a low-corrosion-effect flame brazing auxiliary aluminum flux. Background Technology

[0002] Traditional chloride-based aluminum fluxes, such as the common LiCl-KCl-ZnCl2 system, while possessing high activity and meeting the need for oxide film removal during welding to some extent, have serious drawbacks. The Cl⁻ ions in their post-weld residue can trigger strong electrochemical corrosion, damaging the welded aluminum and aluminum alloy components and affecting their service life and performance stability. Furthermore, some chloride-based flux formulations also contain heavy metal components such as PbCl2 and CdCl2, which not only pose a threat to the health of operators but also bring great environmental pressure to the waste disposal process, making it difficult to meet the increasingly stringent environmental regulations. Fluoride-based aluminum fluxes, represented by KAlF4, outperform chloride-based fluxes in terms of post-weld residue corrosion. However, their activation temperature is high, typically requiring ≥558℃ to function effectively. This high temperature not only increases energy consumption but also easily leads to overheating of the base material, limiting their application in actual production. More importantly, these fluxes are extremely sensitive to the magnesium content in aluminum alloys. When the magnesium content in the aluminum alloy is >0.5%, the activity of the flux and the welding effect will decrease significantly, failing to meet the welding requirements of many magnesium-containing aluminum alloy materials. For example, the application of fluoride-based fluxes is greatly limited in the welding of commonly used magnesium-containing aluminum alloy components such as automotive aluminum alloy radiators and air conditioning heat exchangers. In addition, both powdered and paste-like traditional fluxes have their own drawbacks. Powdered fluxes are easily blown away by the flame during flame brazing, resulting in flux waste and difficulty in ensuring consistent welding quality. Paste-like fluxes, on the other hand, generally suffer from insufficient stability and are prone to layering and hardening during storage, leading to uneven distribution of their effective components, affecting welding performance. Their storage period is often short, causing inconvenience for material management in manufacturing enterprises.

[0003] In summary, this invention provides a flame brazing auxiliary aluminum flux with low corrosion effect. Summary of the Invention

[0004] In order to overcome the above-mentioned defects of the prior art, the present invention provides a flame brazing auxiliary aluminum flux with low corrosion effect to solve the problems mentioned in the background art.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a low-corrosion flame brazing auxiliary aluminum flux, comprising the following components by mass percentage: Potassium fluoroaluminate 35-45% and cesium fluoroaluminate 10-15% form a eutectic matrix at 490-520℃; A dual-activity enhancement system consisting of 5-8% lithium fluoride and 3-6% zinc fluoride is used to dissolve composite oxide films of alumina and magnesium oxide by utilizing the synergistic effect of fluoride ions and zinc ions. Potassium chloride 20-25% is used as an interface regulator to optimize ion migration channels; Hydroxypropyl methylcellulose (0.5-1.5%) and propylene glycol-polyethylene glycol (15-20%) form a smart thixotropic carrier, achieving stability over a wide temperature range from -10℃ to 50℃.

[0006] Preferably, the potassium fluoroaluminate and cesium fluoroaluminate are activated by microwave plasma to form an amorphous eutectic precursor with an amorphization degree ≥85%, the eutectic peak temperature is controlled at 505±5℃, and the release of active fluorine ions is increased by 40%.

[0007] Preferably, the zinc fluoride and lithium fluoride are pulverized in a supersonic fluidized bed to form nanocomposite particles with a particle size ≤15μm, which generate an active zinc fluoride-lithium fluoride film in situ on the aluminum alloy surface with an interfacial tension ≤0.065N / m, breaking through the limitation of magnesium content ≤0.5% to Mg≤2.0%.

[0008] Preferably, the potassium chloride is treated with lattice defect engineering to form a layered structure, which increases the ion migration rate to 0.07 S / cm and the spreading area to ≥280 mm², thereby improving the flux flowability.

[0009] Preferably, the intelligent thixotropic carrier is modified with an amphiphilic block copolymer to form a temperature-sensitive micelle network, which maintains thixotropy in an environment of -10℃ to 50℃, has no splashing when the heat flux is 50kW / m², and has a construction thickness of ≤0.08mm.

[0010] This invention also provides a method for preparing a flame brazing auxiliary aluminum flux with low corrosion effect, specifically including the following steps: S1. Eutectic matrix activation: Potassium fluoroaluminate and cesium fluoroaluminate are mixed at a ratio of 3:1 to 4:1 and treated in a microwave plasma reactor with a power of 1.2kW and an argon flow rate of 5L / min for 10min to form an amorphous precursor. S2, modified with dual-activity enhancers, zinc fluoride, lithium fluoride and nano silica with 1-butyl-3-methylimidazolium tetrafluoroborate grafted on the surface are fed into a supersonic fluidized bed pulverizer with a pressure of 4.0 MPa and a speed of 12000 rpm to form core-shell structured composite particles, wherein the particle size of nano silica is 20-30 nm. S3. Interfacial control agent treatment: potassium chloride is calcined at 800℃ in an argon atmosphere for 2 hours to form a layered structure. S4. Intelligent thixotropic carrier configuration: Hydroxypropyl methylcellulose and propylene glycol-polyethylene glycol are dispersed at 60℃ and 400W ultrasonic conditions for 30 minutes to form a temperature-sensitive micelle network. S5. Paste forming: Mix the powders from S1-S3 with the carrier from S4 at a ratio of 7:3, and then heat at a shear rate of 8000 s⁻¹. -1 The mixture was vacuum-stirred in a dual planetary mixer for 60 minutes, and then cured by gradient cooling with a 20kHz, 1.2T pulsed electromagnetic field.

[0011] Preferably, in step S2, the grafting rate of nano-silica is ≥1.2 mmol / g, and monodispersity is achieved through the synergistic effect of electrostatic repulsion and steric hindrance, forming a nano-layered reinforcing phase in the eutectic matrix, thereby increasing the thermal conductivity by 28%.

[0012] Preferably, in step S5, the pulsed electromagnetic field induces the inorganic particles to oriented and form a honeycomb lubricating film structure with a storage modulus G' ≥ 5000 Pa, ensuring storage stability from -10℃ to 50℃.

[0013] Preferably, it also includes S6 environmental protection treatment: Hollow fiber membrane modules with a pore size of 0.1 μm and a molecular weight cutoff of 3000 are used to recover fluoride tail gas, with a fluoride recovery rate of ≥98%. 95% of the free water in the carrier was removed by vacuum freeze drying at -50℃ and 0.01mbar, while retaining the three-dimensional network structure of hydroxypropyl methylcellulose.

[0014] Preferably, the tensile strength of the brazed weld is ≥195MPa, and the airtightness is ≤8×10⁻⁶. -10 Pa・m³ / s, post-weld residue pH value 7.2-7.8, welding time shortened by 30%.

[0015] The technical effects and advantages of this invention are as follows: This invention utilizes a specific ratio of potassium fluoroaluminate and cesium fluoroaluminate to form a eutectic matrix at 490-520℃, combined with a dual-activity enhancement system of lithium fluoride and zinc fluoride. This system can efficiently dissolve composite oxide films of alumina and magnesium oxide. When flame brazing aluminum alloys with a magnesium content as high as 1.8%, the weld tensile strength reaches 196-200 MPa, and the airtightness is as low as 7 × 10⁻⁶ MPa. -10 -8×10 -10 Pa・m³ / s, far exceeding the limitations of traditional flux on magnesium content and welding quality standards, greatly expands the material range for aluminum alloy welding and meets the needs of industries with stringent welding quality requirements, such as aerospace and automotive manufacturing. The flux of this invention eliminates the corrosive component containing Cl⁻ found in traditional chloride-type fluxes. The pH value of the post-soldering residue is between 7.3 and 7.5, which is close to neutral, exhibiting extremely low corrosivity. At the same time, the use of membrane contactor technology to recover fluoride tail gas and vacuum freeze drying to remove more than 95% of the free water in the carrier not only reduces environmental pollution but also avoids complex post-soldering cleaning processes, lowers production costs, and conforms to the current trend of green manufacturing. In the preparation process, this invention employs steps such as microwave plasma activation treatment and supersonic fluidized bed pulverization to optimize the microstructure and performance of the flux. Compared with traditional fluxes, the flux welding time is significantly shortened by 30.5%-32%. In industrial production, this can significantly improve production efficiency, increase product output per unit time, bring higher economic benefits to enterprises, and enhance their competitiveness in the market. Attached Figure Description

[0016] Figure 1 This is the overall flowchart of the present invention. Detailed Implementation Example

[0017] This embodiment provides a low-corrosion flame brazing auxiliary aluminum flux, which is accurately weighed according to the following mass percentages: 40% potassium fluoroaluminate, 12% cesium fluoroaluminate, 6% lithium fluoride, 4% zinc fluoride, 22% potassium chloride, 1% hydroxypropyl methylcellulose, and 15% propylene glycol-polyethylene glycol.

[0018] Specifically, the preparation steps include the following: S1. Eutectic matrix activation: Potassium fluoroaluminate and cesium fluoroaluminate were mixed in a ratio of 3.3:1 and placed in a microwave plasma reactor with a power of 1.2 kW and an argon flow rate of 5 L / min for 10 min to obtain an amorphous eutectic precursor. The amorphization degree was measured to be 87%. S2, modified with dual-activity enhancers, involves adding zinc fluoride, lithium fluoride, and 25nm nano-silica grafted with 1-butyl-3-methylimidazolium tetrafluoroborate to a supersonic fluidized bed pulverizer at 4.0 MPa and 12000 rpm to form core-shell composite particles. Testing showed that the nano-silica grafting rate was 1.3 mmol / g. S3. Interfacial conditioning: Potassium chloride was calcined at 800℃ in an argon atmosphere for 2 hours to form a layered structure. Measurements showed that the ion migration rate increased to 0.072 S / cm. S4. Intelligent thixotropic carrier configuration: Hydroxypropyl methylcellulose and propylene glycol-polyethylene glycol were dispersed at 60℃ and 400W ultrasonic conditions for 30 minutes to successfully form a temperature-sensitive micelle network. S5. Paste forming: Mix the powders from S1-S3 with the carrier from S4 at a ratio of 7:3, and then heat at a shear rate of 8000 s⁻¹. -1 The mixture was vacuum-stirred in a dual planetary mixer for 60 min, followed by gradient cooling under a 20 kHz, 1.2 T pulsed electromagnetic field. The resulting paste exhibited a honeycomb-like lubricating film structure formed by inorganic particles, with a storage modulus G' of 5200 Pa. S6. Environmentally friendly treatment: Hollow fiber membrane modules with a pore size of 0.1μm and a molecular weight cutoff of 3000 are used to recover fluorides from the exhaust gas of the gas pulverizer, achieving a fluoride recovery rate of 98.5%; 95.5% of the free water in the carrier is removed by vacuum freeze drying at -50℃ and 0.01mbar, while retaining the three-dimensional network structure of hydroxypropyl methylcellulose.

[0019] Performance testing: Flame brazing of an aluminum alloy with a magnesium content of 1.5% was performed using the flux described in this embodiment. The results showed that the tensile strength of the brazed weld was 200 MPa and the airtightness was 7 × 10⁻⁶. -10 Pa・m³ / s, post-weld residue pH value of 7.5, and welding time reduced by 32% compared to traditional flux. Example

[0020] This embodiment provides a low-corrosion flame brazing auxiliary aluminum flux, which comprises 38% potassium fluoroaluminate, 13% cesium fluoroaluminate, 7% lithium fluoride, 5% zinc fluoride, 23% potassium chloride, 0.8% hydroxypropyl methylcellulose, and 13.2% propylene glycol-polyethylene glycol by mass percentage.

[0021] Specifically, the preparation steps include the following: S1. Eutectic matrix activation: Potassium fluoroaluminate and cesium fluoroaluminate were mixed at a ratio of 3.6:1 and treated in a microwave plasma reactor for 10 min. The degree of amorphization was 86%, the eutectic peak temperature was 503℃, the power was 1.2kW, and the argon flow rate was 5L / min. S2, modified with dual-activity enhancers, zinc fluoride, lithium fluoride and nano-silica with a particle size of 22nm grafted with 1-butyl-3-methylimidazolium tetrafluoroborate were fed into an ultrasonic fluidized bed pulverizer. The nano-silica grafting rate was 1.25mmol / g, forming core-shell structured composite particles. The ultrasonic fluidized bed pulverizer had a pressure of 4.0MPa and a speed of 12000rpm. S3. Interfacial regulator treatment: Potassium chloride was calcined at 800℃ in an argon atmosphere for 2 hours to form a layered structure with an ion migration rate of 0.071S / cm and a spreading area of ​​290mm². S4. Intelligent thixotropic carrier configuration: Hydroxypropyl methylcellulose and propylene glycol-polyethylene glycol are dispersed at 60℃ and 400W ultrasonic conditions for 30 minutes to form a temperature-sensitive micelle network. At a heat flux of 50kW / m², the paste does not splatter and the application thickness is 0.07mm. S5. Paste Forming: Mix the powders from S1-S3 with the carrier from S4 at a 7:3 ratio, vacuum stir in a dual planetary mixer for 60 minutes, then cure by gradient cooling under a 20kHz, 1.2T pulsed electromagnetic field. The storage modulus G' is 5100Pa, and the shear rate of the dual planetary mixer is 8000s. -1 ; S6. Environmentally friendly treatment: Hollow fiber membrane modules are used to recover fluoride tail gas with a fluoride recovery rate of 98.2%; Vacuum freeze drying removes 95.2% of free water from the carrier while retaining the three-dimensional network structure of hydroxypropyl methylcellulose.

[0022] Performance testing: Flame brazing of an aluminum alloy with a magnesium content of 1.8% using the flux described in this embodiment yielded a weld tensile strength of 198 MPa and an airtightness of 8 × 10⁻¹. 0 Pa・m³ / s, post-weld residue pH value 7.4, welding time shortened by 31%. Example

[0023] This embodiment provides a low-corrosion flame brazing auxiliary aluminum flux, which comprises 42% potassium fluoroaluminate, 11% cesium fluoroaluminate, 5.5% lithium fluoride, 3.5% zinc fluoride, 21% potassium chloride, 1.2% hydroxypropyl methylcellulose, and 16.8% propylene glycol-polyethylene glycol by mass percentage.

[0024] Specifically, the preparation steps include the following: S1. Eutectic matrix activation: Potassium fluoroaluminate and cesium fluoroaluminate were mixed at a ratio of 3.8:1 and treated in a microwave plasma reactor for 10 min. The degree of amorphization was 85.5%, the eutectic peak temperature was 507℃, the power was 1.2kW, and the argon flow rate was 5L / min. S2, Dual-activity enhancer modification: Zinc fluoride, lithium fluoride and nano-silica with a particle size of 28nm and grafted with 1-butyl-3-methylimidazolium tetrafluoroborate were added to an ultrasonic fluidized bed pulverizer. The grafting rate of nano-silica was 1.22mmol / g, forming core-shell structured composite particles. The pressure of the ultrasonic fluidized bed pulverizer was 4.0MPa and the rotation speed was 12000rpm. S3, interface regulator treatment: potassium chloride was calcined at 800℃ in an argon atmosphere for 2 hours to form a layered structure with an ion migration rate of 0.073 S / cm and a spreading area of ​​285 mm². S4. Intelligent thixotropic carrier configuration: Hydroxypropyl methylcellulose and propylene glycol-polyethylene glycol are dispersed at 60℃ and 400W ultrasonic conditions for 30 minutes to form a temperature-sensitive micelle network. S5. Paste Forming: Mix the powders from S1-S3 with the carrier from S4 at a 7:3 ratio, vacuum stir for 60 minutes in a dual planetary mixer, and then cure by gradient cooling under a 20kHz, 1.2T pulsed electromagnetic field. The storage modulus G' is 5050Pa, and the shear rate of the dual planetary mixer is 8000s. -1 ; S6. Environmentally friendly treatment: hollow fiber membrane modules are used to recover fluoride tail gas with a fluoride recovery rate of 98.3%; through vacuum freeze drying, 95.3% of free water in the carrier is removed, while retaining the three-dimensional network structure of hydroxypropyl methylcellulose.

[0025] Performance testing: Flame brazing of an aluminum alloy with a magnesium content of 1.6% using the flux described in this embodiment yielded a weld tensile strength of 196 MPa and an airtightness of 7.5 × 10⁻⁶ MPa. -10 Pa・m³ / s, post-weld residue pH value 7.3, welding time shortened by 30.5%.

[0026] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A low-corrosion flame brazing auxiliary aluminum flux, characterized in that: It includes the following components by mass percentage: Potassium fluoroaluminate 35-45% and cesium fluoroaluminate 10-15% form a eutectic matrix at 490-520℃; A dual-activity enhancement system consisting of 5-8% lithium fluoride and 3-6% zinc fluoride is used to dissolve composite oxide films of alumina and magnesium oxide by utilizing the synergistic effect of fluoride ions and zinc ions. Potassium chloride 20-25% was used as an interface modifier to optimize ion migration channels; Hydroxypropyl methylcellulose (0.5-1.5%) and propylene glycol-polyethylene glycol (15-20%) form a smart thixotropic carrier, achieving stability over a wide temperature range from -10℃ to 50℃.

2. The low-corrosion flame brazing auxiliary aluminum flux according to claim 1, characterized in that: The potassium fluoroaluminate and cesium fluoroaluminate are activated by microwave plasma to form an amorphous eutectic precursor with an amorphization degree ≥85%, the eutectic peak temperature is controlled at 505±5℃, and the release of active fluorine ions is increased by 40%.

3. The low-corrosion flame brazing auxiliary aluminum flux according to claim 1, characterized in that: The zinc fluoride and lithium fluoride are pulverized in a supersonic fluidized bed to form nanocomposite particles with a particle size ≤15μm, which generate an active zinc fluoride-lithium fluoride film in situ on the aluminum alloy surface with an interfacial tension ≤0.065N / m, breaking through the limitation of magnesium content ≤0.5% to Mg≤2.0%.

4. The low-corrosion flame brazing auxiliary aluminum flux according to claim 1, characterized in that: The potassium chloride is treated with lattice defect engineering to form a layered structure, which increases the ion migration rate to 0.07 S / cm and the spreading area to ≥280 mm², thereby improving flux flowability.

5. The low-corrosion flame brazing auxiliary aluminum flux according to claim 1, characterized in that: The intelligent thixotropic carrier is modified with amphiphilic block copolymer to form a temperature-sensitive micelle network, which maintains thixotropy in an environment of -10℃ to 50℃, has no splashing when the heat flux is 50kW / m², and has a construction thickness of ≤0.08mm.

6. The low-corrosion flame brazing auxiliary aluminum flux according to claim 1, characterized in that: Specifically, the following steps are included: S1. Eutectic matrix activation: Potassium fluoroaluminate and cesium fluoroaluminate are mixed at a ratio of 3:1 to 4:1 and treated in a microwave plasma reactor with a power of 1.2kW and an argon flow rate of 5L / min for 10min to form an amorphous precursor. S2, modified with dual-activity enhancers, zinc fluoride, lithium fluoride and nano silica with 1-butyl-3-methylimidazolium tetrafluoroborate grafted on the surface are fed into a supersonic fluidized bed pulverizer with a pressure of 4.0 MPa and a speed of 12000 rpm to form core-shell structured composite particles, wherein the particle size of nano silica is 20-30 nm. S3. Interfacial control agent treatment: potassium chloride is calcined at 800℃ in an argon atmosphere for 2 hours to form a layered structure. S4. Intelligent thixotropic carrier configuration: Hydroxypropyl methylcellulose and propylene glycol-polyethylene glycol are dispersed at 60℃ and 400W ultrasonic conditions for 30 minutes to form a temperature-sensitive micelle network. S5. Paste forming: Mix the powders from S1-S3 with the carrier from S4 at a ratio of 7:3, and then heat at a shear rate of 8000 s⁻¹. -1 The mixture was vacuum-stirred in a dual planetary mixer for 60 minutes, and then cured by gradient cooling with a 20kHz, 1.2T pulsed electromagnetic field.

7. The low-corrosion flame brazing auxiliary aluminum flux according to claim 6, characterized in that: In step S2, the grafting rate of nano-silica is ≥1.2 mmol / g. Monodispersion is achieved through the synergistic effect of electrostatic repulsion and steric hindrance, forming a nano-layered reinforcing phase in the eutectic matrix, which improves thermal conductivity by 28%.

8. The low-corrosion flame brazing auxiliary aluminum flux according to claim 6, characterized in that: In step S5, the pulsed electromagnetic field induces the inorganic particles to oriented and form a honeycomb lubricating film structure with a storage modulus G'≥5000Pa, ensuring storage stability from -10℃ to 50℃.

9. The low-corrosion flame brazing auxiliary aluminum flux according to claim 6, characterized in that: It also includes S6 environmental protection treatment: Hollow fiber membrane modules with a pore size of 0.1 μm and a molecular weight cutoff of 3000 are used to recover fluoride tail gas, with a fluoride recovery rate of ≥98%. 95% of the free water in the carrier was removed by vacuum freeze drying at -50℃ and 0.01mbar, while retaining the three-dimensional network structure of hydroxypropyl methylcellulose.

10. The low-corrosion flame brazing auxiliary aluminum flux according to claim 1, characterized in that: After brazing, the tensile strength of the weld is ≥195MPa, and the airtightness is ≤8×10⁻⁶. -10 Pa・m³ / s, post-weld residue pH value 7.2-7.8, welding time shortened by 30%.